(untitled) (Journal of Comparative Social Work, 2016)
Over the past two decades, several measures have been developed to provide assistance to persons defined as victims of trafficking. This article describes and discusses the organization of barriers and access to assistance (such as housing, medical assistance and subsistence support) for this group in Norway, taking as its starting point the daily practice of social workers and using an institutional ethnographic approach. Of great significance to access to assistance are the different administrative statuses that trafficking victims are assigned and move between, thus having rights granted or taken away. The negotiation of these administrative categories and navigation of conflicting legislation become a central aspect of social workers’ daily practice. Persons defined as ‘trafficking victims’ are eligible for a special residence permit, while assistance in Norway in practice is provided through the universal welfare system. ‘Human trafficking’ and ‘trafficking victim’ are operational categories in criminal law and immigration legislation, but they are not administrative categories for welfare provision. Instead, being defined as a trafficking victim functions as an inroad to assignation of other administrative categories (also dependent on residence and registration statuses) that determine what assistance is or is not available. Gaps and inconsistencies between institutional and legal complexes arise when one small group of people are awarded special measure rights within a universal system, creating a bureaucratically complicated and ‘messy’ path to assistance. This ‘messiness’ does not mean that it does not always work. However, it appears to work best for those who fit well with the modern Norwegian bureaucracy, e.g. in terms of being able to document identity and stay within one administrative status, and worst for those who do not. Hence, the system for victim assistance appears to be the least accessible for some of the least privileged members of the group it is intended for.